ANALISIS EFISIENSI USAHATANI JAMBU METE (Anacardicum occidentale L) DI DESA KRINGA KECAMATAN TALIBURA KABUPATEN SIKKA - Fiator Nong; Yovita Yasintha Bolly; Oktaviana Rosario Sere Gili (Agriculture - Jurnal Ilmu Pertanian, 2023)
The research was conducted in Kringa Village, Talibura District, Sikka Regency, in December 2022. The purpose of this study was to determine the amount of revenue, costs, and income obtained by farmers in cashew farming, as well as to analyze the level of profit and efficiency of cashew farming in Kringa Village, Talibura District, Sikka Regency. The research location was determined purposively, considering that Kringa Village is one of the villages where cashew plants are cultivated. The results showed that the lowest income obtained by respondent farmers from cashew farming was IDR 4,088,000, while the highest income reached IDR 21,702,000, with an average income of IDR 8,650,690. The efficiency analysis indicated that cashew farming had an R/C Ratio value of 24, meaning that every expenditure of IDR 1 generated a revenue of IDR 24. This result indicates that cashew farming in the study area is highly profitable and economically efficient.